1989
DOI: 10.1016/s0022-5347(17)40749-x
|View full text |Cite
|
Sign up to set email alerts
|

Bulbocavernosus Reflex: Its Validity as a Diagnostic Test of Neurogenic Impotence

Abstract: Measurement of the bulbocavernosus reflex is used widely to diagnose underlying neurogenic disorders in erectile dysfunction. A prolonged bulbocavernosus reflex latency (that is more than 45 msec.) or the absence of a reflex response of the bulbocavernosus muscles during electrical stimulation of the glans penis is considered a sign of neurological disease. Since only a few experimental studies have been performed in man related to the neurophysiological mechanism of erection, and since the results of these st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
6

Year Published

1990
1990
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(14 citation statements)
references
References 22 publications
1
7
0
6
Order By: Relevance
“…The results suggest that the discovery of an increased BCR and/or PER latency, even with an associated neurological abnormality, does not always imply that impotence is neurogenic: 4 of our patients with abnormal BCR are not impotent and 10 patients with abnormal BCR and/or PER but no relevant neuro logical cause had a vascular abnormality that could explain the impotence. Similar results were found by Lavoisier et al [14] and Desai et al [15]. A questionable relationship between an abnormal BCR and impotence was also found in a previous study which showed that 6 of 10 perfectly potent diabetic men had nevertheless an increased BCR and/or PER latency [19].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The results suggest that the discovery of an increased BCR and/or PER latency, even with an associated neurological abnormality, does not always imply that impotence is neurogenic: 4 of our patients with abnormal BCR are not impotent and 10 patients with abnormal BCR and/or PER but no relevant neuro logical cause had a vascular abnormality that could explain the impotence. Similar results were found by Lavoisier et al [14] and Desai et al [15]. A questionable relationship between an abnormal BCR and impotence was also found in a previous study which showed that 6 of 10 perfectly potent diabetic men had nevertheless an increased BCR and/or PER latency [19].…”
Section: Discussionsupporting
confidence: 84%
“…Two main rea sons may explain this odd relationship. The first one is that BCR is testing myelinated sensory and motor fibers of pudendal nerves which have been demonstrated to play an important part in sexual function [14,20,21]. Nevertheless, erection primarily depends on the integ rity of small nonmyelinated parasympathic fibers which are not tested by the BCR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(BCR-L) measurements and (pudSSEP) recordings M Fabra and H Porst Another issue worthwhile being discussed is the interpretation of several authors, that in patients with normal Rigiscan but pathological BCR-L andaor pudendal SSEP, the etiology of impotence should be considered psychogenic as the Rigiscan recordings could disprove the neurophysiological investigations. 2,3 Concerning these statements it must be realised, that the occurrence of nocturnal penile reactions and voluntarily penile erections, induced by sexual arousal, are subject of activation of completely different neurological pathways and are therefore hardly comparable to each other; 58 further remarks to the method of penile tumescence measuring are given by Goldstein. 59 Furthermore, normal nocturnal erections will occur, when the efference from the spinal cord to the penis is intact, BCR-L and pudendal SSEP however may be just pathological, when the afference from the penis to spinal cord is impaired.…”
Section: ±55mentioning
confidence: 99%
“…L'étude de la latence du réflexe bulbocaverneux n'est pas très contributive au diagnostic d'atteinte du nerf dorsal de la verge [17][18][19][20][21][22]. En effet, le trajet anatomique de l'arc réflexe nerf pudendal-S2, S3, S4 que teste la latence sacrée est long, et une atteinte purement distale du nerf pudendal, qui plus est uniquement sensitive, ne suffit pas le plus souvent à allonger la latence qui peut, par ailleurs, être altérée du fait d'une lésion radiculomédullaire ou plexique [23][24][25]. Dans notre série, elle était perturbée dans seulement 20 % des cas.…”
Section: Discussionunclassified